Functional Activation in the Ventral Object Processing Pathway during the First Year - Wilcox, Teresa; Biondi, Marisa (Frontiers in Systems Neuroscience, 2016)
Infants' capacity to represent objects in visual working memory changes substantially during the first year of life. There is a growing body of research focused on identifying neural mechanisms that support this emerging capacity, and the extent to which visual object processing elicits different patterns of cortical activation in the infant as compared to the adult. Recent studies have identified areas in temporal and occipital cortex that mediate infants' developing capacity to track objects on the basis of their featural properties. The current research (Experiments 1 and 2) assessed patterns of activation in posterior temporal cortex and occipital cortex using fNIRS in infants 3 to 13 months of age as they viewed occlusion events. In the occlusion events, either the same object or featurally distinct objects emerged to each side of a screen. The outcome of these studies, combined, revealed that in infants 3 to 6 months, posterior temporal cortex was activated to all events, regardless of the featural properties of the objects and whether the event involved one object or two (featurally distinct) objects. Infants 7 to 8 infants months showed a waning posterior temporal response and by 10 to 13 months this response was negligible. Additional analysis showed that the age groups did not differ in their visual attention to the events and that changes in HbO were better explained by age in days than head circumference. In contrast to posterior temporal cortex, robust activation was obtained in occipital cortex across all ages tested. One interpretation of these results is that they reflect pruning of the visual object-processing network during the first year. The functional contribution of occipital and posterior temporal cortex, along with higher-level temporal areas, to infants' capacity to keep track of distinct entities in visual working memory is discussed.